2006
DOI: 10.1029/2005ja011413
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray emission from the outer planets: Albedo for scattering and fluorescence of solar X rays

Abstract: [1] Soft X-ray emission has been observed from the low-latitude ''disk'' of both Jupiter and Saturn as well as from the auroral regions of these planets. The disk emission as observed by ROSAT, the Chandra X-Ray Observatory, and XMM-Newton appears to be uniformly distributed across the disk and to be correlated with solar activity. These characteristics suggest that the disk X rays are produced by (1) the elastic scattering of solar X rays by atmospheric neutrals and (2) the absorption of solar X rays in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 32 publications
5
60
0
Order By: Relevance
“…More recent Chandra observations have provided us with a remarkable view of the X-ray morphology of the Saturnian system, and of its temporal behaviour in the X-rays: both the planet's disk and the rings have been separately detected, and strong variability, closely following the behaviour of the solar X-ray flux, has been discovered in the disk X-ray emission (Bhardwaj et al 2005a,b). This suggests that its origin may lie in the scattering of solar X-rays in the upper layers of Saturn's atmosphere, as is the case for Jupiter's disk emission (Bhardwaj et al 2005cCravens et al 2006). Unlike Jupiter, though, no difference is found in the spectral characteristics of Saturn's disk and polar emissions, thus no evidence for X-rays of auroral origin is provided by the Chandra data.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…More recent Chandra observations have provided us with a remarkable view of the X-ray morphology of the Saturnian system, and of its temporal behaviour in the X-rays: both the planet's disk and the rings have been separately detected, and strong variability, closely following the behaviour of the solar X-ray flux, has been discovered in the disk X-ray emission (Bhardwaj et al 2005a,b). This suggests that its origin may lie in the scattering of solar X-rays in the upper layers of Saturn's atmosphere, as is the case for Jupiter's disk emission (Bhardwaj et al 2005cCravens et al 2006). Unlike Jupiter, though, no difference is found in the spectral characteristics of Saturn's disk and polar emissions, thus no evidence for X-rays of auroral origin is provided by the Chandra data.…”
Section: Introductionmentioning
confidence: 60%
“…As expected, there appears to be correlation between Saturn's disk X-ray power and the solar X-ray flux. For comparison, the same parameters are also plotted for Jupiter's disk (filled circles), which also has been shown to act as a mirror of solar X-rays (Maurellis et al 2000;Bhardwaj et al 2005c;Cravens et al 2006). XMM-Newton and Chandra observations in Fig.…”
Section: Separating Saturn's Disk and Rings X-ray Emissionmentioning
confidence: 99%
“…4: OVII photons are well separated spatially into the two aurorae, while the other lines are filling in the low latitude/cross dispersion range. In particular, this is true for the FeXVII lines at 15 and 17 Å, which are known to be associated with the planet's disk and are thought to be scattered solar X-rays (BR1, Maurellis et al 2000;Cravens et al 2006). Unfortunately, the combination of lower RGS sensitivity and low source flux at the short and long wavelength ends of the instrument operational range is such that Jupiter's spectrum is only significantly detected in the range 13−23 Å (0.54−0.95 keV), to which we have restricted subsequent spectral fitting.…”
Section: Rgs Spectramentioning
confidence: 99%
“…The line is likely to be residual contamination by the disk emission, which may become more evident above ∼1 keV where the ion contribution to the auroral emission is decreasing rapidly. We know that the disk acts as a mirror for solar X-rays (Maurellis et al 2000, Cravens et al 2006): Bhardwaj et al (2005 have shown that a very large solar flare took place at a time such that Jupiter's response to it would have been observable by XMM-Newton had it not been switched off during perigee passage between revs 0726 and 0727. Possibly part of this response to the flare, Jupiter's disk emission is seen to be overall brighter by ∼40%, and the flux of the MgXI line from the disk to be three times larger, in rev.…”
Section: The Ion Componentmentioning
confidence: 99%
See 1 more Smart Citation